2020
DOI: 10.2147/cia.s271969
|View full text |Cite
|
Sign up to set email alerts
|

<p>Associations of Postoperative Complications Assessed by Clavien–Dindo Classification and Comprehensive Complication Index with Long-Term Overall Survival in Elderly Patients after Radical CRC Resection</p>

Abstract: Background: Advancing age is associated with high incidence of colorectal cancer (CRC) and high rates of postoperative complications (POCs). However, the impact of of POC severity-evaluated by Clavien-Dindo classification (CDC) or comprehensive complication index (CCI)-on long-term overall survival (OS) in elderly patients after radical CRC resection is not clear. Methods: Elderly patients aged 65 years or more with CRC undergoing radical resection were retrospectively recruited. POC details were collected and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Studies have shown that POCs can reduce the long-term survival outcome of colorectal cancer [16][17][18]; the same trend has also been observed in gastric cancer [9,19,20].…”
Section: Discussionsupporting
confidence: 52%
“…Studies have shown that POCs can reduce the long-term survival outcome of colorectal cancer [16][17][18]; the same trend has also been observed in gastric cancer [9,19,20].…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, there is growing evidence that postoperative complications not only have a direct impact on short-term outcomes but also impact systemic inflammatory response, which may adversely affect the oncological outcome [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The JCOG0404 study (20) did not prove the non-inferiority of laparoscopy to open surgery, but it did show a decrease in complications, length of hospital stay, and blood loss. There is a report that less postoperative complications affect the difference in survival rate (21), and in this study, age and postoperative complications may have affected the survival rate. HALS may be a surgical technique that incorporates the advantages of both CL and LAP, and although a comparative study of the three surgical techniques is needed in the future, HALS is considered to be useful for patients over 80 years old.…”
Section: Discussionmentioning
confidence: 61%